Characterisation of anti‐alpha toxin antibody levels and colonisation status after administration of an investigational human monoclonal antibody, MEDI4893, against Staphylococcus aureus alpha toxin. Issue 1 (23rd January 2018) - Ruzin, Alexey; Wu, Yuling; Yu, Li; Yu, Xiang‐Qing; Tabor, David E; Mok, Hoyin; Tkaczyk, Christine; Jensen, Kathryn; Bellamy, Terramika; Roskos, Lorin; Esser, Mark T; Jafri, Hasan S
Abstract: Objectives: MEDI4893 is a novel, long‐acting human monoclonal antibody targeting Staphylococcus aureus (SA) alpha toxin (AT). This report presents the results of the exploratory analyses from a randomised phase 1 dose‐escalation study in healthy human subjects receiving single intravenous MEDI4893 doses or placebo. Methods: Anti‐AT antibodies and AT expression were measured as described previously. Nasal swabs were analysed by culture and PCR. Data were summarised by treatment groups and visits by using SAS System Version 9.3. Results: Subjects receiving 2250 or 5000 mg of MEDI4893 had the highest serum anti‐AT neutralising antibody (NAb) levels: approximately 180‐ to 240‐, 70‐ to 100‐ and sevenfold to 10‐fold higher than respective baseline levels at peak, 30 and 360 days, respectively. In these subjects, levels of serum anti‐AT NAbs were >3.2 International Units (IU) mL −1 for at least 211 days. In the upper respiratory tract, anti‐AT NAb levels increased with MEDI4893 dose. No apparent effect of MEDI4893 on SA nasal colonisation, hla gene sequence or AT expression was observed. Five AT variants were detected, their lytic activity was fully neutralised by MEDI4893. Discussion: Our results indicate that (1) MEDI4893 administration at 2250 and 5000 mg would provide effective immunoprophylaxis against systemic SA disease; (2) MEDI4983 distributes to the upper respiratory tract and retains neutralising activity against AT; and (3) potential for emergence of MEDI4893 resistance is low. Conclusion: Intravenous administration of MEDI4893 maintained levels of anti‐AT NAbs in serum and nasal mucosa that may provide effective immunoprophylaxis against SA disease and support continued clinical development of MEDI4893. Abstract : MEDI4893 is a novel, long‐acting human monoclonal antibody targeting Staphylococcus aureus alpha toxin. This report presents the results of the exploratory analyses from MEDI4893 phase 1 study in healthy human subjects. Upon administration of MEDI4893, serum anti‐alpha toxin neutralizing antibody levels increased and were above 3.2 International Units (IU) mL −1 for at least 211 days in subjects receiving 2250 or 5000 mg of MEDI4893, which may provide effective immunoprophylaxis against S. aureus disease and supports continued clinical development of MEDI4893.